2021
DOI: 10.1097/gco.0000000000000732
|View full text |Cite
|
Sign up to set email alerts
|

The obstetric patient in the Covid pandemic: anaesthesia and perioperative care

Abstract: Purpose of review : The Coronavirus Disease 2019 (COVID-19) pandemic has had an unprecedented impact on pregnant women, maternity services and healthcare workers. We review recent literature on the course of COVID-19 infection in pregnancy, and recommendations for treatment and service provision. Recent findings It has been increasingly recognised that pregnant women are at higher risk of severe disease associated with COVID-19 infection. Early critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…There is also some concern about using parenteral opioids and the risk of respiratory suppression, especially in women with respiratory compromise [ 71 , 72 ]. The right patient selection with appropriate clinical review and close monitoring of respiratory rate and oxygen saturation should prevent any adverse outcomes.…”
Section: Management Of Deliverymentioning
confidence: 99%
“…There is also some concern about using parenteral opioids and the risk of respiratory suppression, especially in women with respiratory compromise [ 71 , 72 ]. The right patient selection with appropriate clinical review and close monitoring of respiratory rate and oxygen saturation should prevent any adverse outcomes.…”
Section: Management Of Deliverymentioning
confidence: 99%
“…Esketamine, a novel N-methyl-D-aspartate (NMDA) receptor antagonist, has garnered attention as an anesthetic with exceptional analgesic properties due to its rapid onset and elimination, preservation of spontaneous breathing, control of circulatory excitation, increased analgesic efficacy compared to ketamine, and a reduced risk of adverse effects [6,7]. Presently, there is no definitive consensus on the utilization of esketamine in the context of laparoscopic resection for benign ovarian tumors, nor is there a consensus on the optimal dosage for achieving maximal efficacy [8,9]. This study aims to evaluate and analyze the differential effects and effectiveness of varying esketamine doses in patients diagnosed with benign ovarian tumors scheduled for laparoscopic resection at our institution.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier in the COVID-19 pandemic, higher maternal death rates were attributed to the rise in CS rates and anesthesia complications in an already compromised maternal inflammatory status [ 13 , 14 ]. Reviewing literature reveals a shift in practice to vaginal birth rather than CS delivery, which is now indicated for obstetrical indications in seropositive mothers [ 15 ]. It was confirmed that fetal distress was widely documented as the indication of CS 92 % of all deliveries[ 10 , 16 ].…”
Section: Introductionmentioning
confidence: 99%